2005
DOI: 10.3346/jkms.2005.20.1.61
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Efficacy of New Blue Light Emitting Diode Phototherapy Compared to Conventional Halogen Quartz Phototherapy for Neonatal Jaundice

Abstract: High intensity light emitting diodes (LEDs) are being studied as possible light sources for the phototherapy of neonatal jaundice, as they can emit high intensity light of narrow wavelength band in the blue region of the visible light spectrum corresponding to the spectrum of maximal bilirubin absorption. We developed a prototype blue gallium nitride LED phototherapy unit with high intensity, and compared its efficacy to commercially used halogen quartz phototherapy device by measuring both in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
1
27
0
3
Order By: Relevance
“…A análise de espectro luminoso não foi realizada. Entretanto, recente estudo laboratorial conduzido por Chang et al em 2005 mostrou diferenças na emissão espectral nesses dois tipos de fototerapia 10 . Enquanto na fototerapia com lâmpada halógena, o espectro de emissão situa-se entre 380 e 600 nm, na fototerapia LED este espectro é bem mais estreito (420 a 500 nm) e coincide com o espectro de absorção de luz pela molécula de bilirrubina (400 a 500 nm).…”
Section: J Pediatr (Rio Junclassified
“…A análise de espectro luminoso não foi realizada. Entretanto, recente estudo laboratorial conduzido por Chang et al em 2005 mostrou diferenças na emissão espectral nesses dois tipos de fototerapia 10 . Enquanto na fototerapia com lâmpada halógena, o espectro de emissão situa-se entre 380 e 600 nm, na fototerapia LED este espectro é bem mais estreito (420 a 500 nm) e coincide com o espectro de absorção de luz pela molécula de bilirrubina (400 a 500 nm).…”
Section: J Pediatr (Rio Junclassified
“…These results suggest that effectiveness of phototherapy does not only depend on the color but also the irradiance of light (11,12). Chang et al (13) reported that LEDs showed a significant higher efficacy of bilirubin photodegradation than the conventional phototherapy both in vitro and in vivo. Contraversial reports concerning efficacy of LED phototherapy show that data related to LED phototherapy is still insufficient for its routine recommendation.…”
Section: Despite Many Potential Benefits Ofmentioning
confidence: 83%
“…7,10 Nevertheless, the majority of them were conducted in vitro, and only two involved newborn infants.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent laboratory study conducted by Chang et al in 2005 demonstrated differences in the spectra emitted by these two types of phototherapy. 10 Whereas the emission spectrum of the halogen lamp lays between 380 and 600 nm, that of the phototherapy LEDs is much narrower (420 to 500 nm) and coincides with the spectrum of light that is absorbed by the bilirubin molecule (400 to 500 nm). Therefore, all of the light emitted by the phototherapy is theoretically utilized in the isomerization of bilirubin, which is not the case with the halogen lamp, since part of its light spectrum lays outside the zone of interaction with bilirubin.…”
mentioning
confidence: 99%